Percepção e vivência da humanização na prática médica: relatos de uma graduação em medicina - Montenegro, Carolina Perez (Universidade Federal de São Carlos, 2025)
Humanization in healthcare aims to preserve the human dignity of those receiving care, reaffirming their rights and responsibilities while upholding the integrity of the physician–patient relationship. Recently, humanized care was incorporated into Brazil’s Organic Health Law, emphasizing the need for medical education to focus on this essential aspect of healthcare. This undergraduate work reflects the journey of a medical student at the Federal University of São Carlos (UFSCar) and is organized into critical and reflective narratives about experiences lived during professional practice throughout medical training. These narratives encourage reflection on the concept of humanization in healthcare, highlighting the importance of empathy in the physician–patient relationship, the recognition of each individual’s dignity, and the need for compassion and respect. The second part of this work presents the student’s Scientific Initiation research, which investigated healthcare professionals’ perception of pain in newborns, aiming to improve and humanize the care provided to this vulnerable population. Thus, this work emphasizes the relevance of the concept of humanization in medical education as a foundation for comprehensive and truly humane care.
Perception and experience of humanization in medical practice: accounts from a medical degree program
Keywords: Educação Médica; Respeito; Humanização da assistência; CIENCIAS DA SAUDE::SAUDE COLETIVA; 3. Saúde e Bem-Estar